Patient Journey Map: Metal Hypersensitivity - J. Adrienne Lagura RN, MN-NP (candidate); Dzifa Dordunoo RN, PhD; Anastasia Mallidou RN, PhD; Jett Carey BScN; Elizabeth M. Borycki RN, PhD; Andre Kushniruk BSc, PhD (Journal of Patient Experience, 2023)
In this study, we highlight patients’ experiences with metal hypersensitivity (MH) after receiving implantable medical devices (IMDs). We aim to identify gaps in clinical care and improve outcomes for individuals who have or may be sensitive to metals. Secondary data analysis from a previous interpretative phenomenological qualitative study was utilized. Using patient journey maps, we explored the experiences of 8 individuals from outpatient settings who received IMD and have first-hand experience with MH. We documented their journey from MH symptom recognition to diagnosis and subsequent IMD management. The results reveal that the time frames from device implantation to the treatment of MH varied from 17 to 228 months. The longest phase on the patient journey maps was the symptom recognition phase, which refers to the time between symptom emergence and MH diagnosis. Participants also required extensive healthcare utilization following their initial surgery. These findings emphasize that MH should be considered in differential diagnoses for patients with IMD. Early screening and detection of MH can enhance patient safety, alleviate distress, and reduce unnecessary healthcare utilization.